2020
DOI: 10.14202/vetworld.2020.1732-1736
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and hypolipidemic activity of combined milk thistle and fenugreek seeds in alloxan-induced diabetic albino rats

Abstract: Background and Aim: Despite the availability of antidiabetic drugs, they are not free from associated adverse side effects. This study aimed to evaluate the hypoglycemic and hypolipidemic effects of oral administration of seeds from two medicinal plants: (1) Milk thistle and (2) fenugreek. Materials and Methods: Plant seeds were washed in distilled water and ground with a coffee grinder. Alloxan was used to induce diabetes in 20 male albino rats. Diabetic rats were randomly divided into two groups: (1) Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Other studies demonstrated that supplementation of animal diets with different forms and concentrations of milk thistle caused muscle pH to increase not only in pigs [ 7 ], but also in broiler chickens [ 40 ] and in rabbits [ 41 ]. This relationship may result from the hyperglycemic action of the active component of milk thistle, i.e., silibinin [ 42 , 43 ]. As reported by Colturato et al [ 44 ], silibinin concentrations of 50–300 µM have a marked effect on carbohydrate metabolism in rat liver by inhibiting gluconeogenesis in the fasted condition as well as glycogenolysis and glycolysis in the fed condition.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies demonstrated that supplementation of animal diets with different forms and concentrations of milk thistle caused muscle pH to increase not only in pigs [ 7 ], but also in broiler chickens [ 40 ] and in rabbits [ 41 ]. This relationship may result from the hyperglycemic action of the active component of milk thistle, i.e., silibinin [ 42 , 43 ]. As reported by Colturato et al [ 44 ], silibinin concentrations of 50–300 µM have a marked effect on carbohydrate metabolism in rat liver by inhibiting gluconeogenesis in the fasted condition as well as glycogenolysis and glycolysis in the fed condition.…”
Section: Resultsmentioning
confidence: 99%
“…Androgens function in the testis to stimulate the development of both Leydig and Sertoli cells. Androgen has opposing effects on adult Leydig cells and adult Sertoli cells, partially suppressing steroid genesis in the former but boosting the latter's actions that are essential for spermatogenesis [48,49] . Serum TH reduction in the present study might be due to a disturbed oxidant antioxidant state [25] .…”
Section: Leydig Cell Number Was Negatively Correlated Withmentioning
confidence: 99%
“…Plant polyphenols and the flavonoids are some of the commonly occurring antidiabetic agents [8]. Trigonella foenum-graecum contributes to lower postprandial hyperglycemia in diabetes the mechanisms of action involves provocation of glucose dependent insulin secretion from beta cells of pancreas along with embarrassment of activity of enzymes like amylase and glucosidase [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera is a famous consumable plant having therapeutic and the nutritive values.Moringa oleifera is also known as Horseradish tree and also called as drumsticktree.It is rich in phytochemicals and minerals [9][10][11]. It is a constituent of folk medicine and helps to cure the diabetes.It is commonly called as Miracle tree.It also helps to control cancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%